The Determinants of Credit Risk Under Dual Banking System: Indonesian Experience Based on Bank Specific Variables - Muhammad Nur Faaiz F. Achsani; Salina Kassim (Department of Islamic Economics, IPB University, 2021)
In Indonesian banking system, conventional banks are operating side by side with Islamic banking in a dual banking system. In terms of the credit risk determinants, Islamic banks should be affected by the different factors as conventional banks. However, the similarity of Islamic banks and the conventional bank in terms of contracts might lead to the opinion the same variables are affecting the performance of Islamic and conventional banks. The objective of the study is to examine and obtain an understanding on how the credit and financing in Indonesian dual banking system responses to changes in bank-specific variables. The main approach to fit the model used in this study is the dynamic panel data. Based on the result of the combined model, there are some independent variables that significantly affect credit risk. Profitability significantly affects credit risk with a negative relationship. While size significantly affects credit risk with a positive relationship. When it comes to the dummy variable, it can be said that the type of bank doesn’t play a significant role in determining the credit risk. In other word, there is no difference between Islamic bank and conventional banks in terms of credit risk. To analyze the crisis effect deeper, we compare the result of conventional banking model 2016-2020 and Islamic banking model 2016-2020. There is no independent variable that significantly affect the credit risk in the conventional banking model 2016-2020, three out of four independent variables affect credit risk significantly in the Islamic banking model 2016-2020. This is because conventional banks tend to play safe by avoiding the disbursement of credit and focusing on derivatives. However, this strategy is not suitable for Islamic banking as they are not allowed to do speculative activities. Islamic banking are still focusing on traditional banking activity.